The impacts on freight train operational performance of new rail infrastructure to segregate passenger and freight traffic. (January 2017) - Woodburn, Allan
Abstract: Rail freight has an important role to play in improving the resource efficiency and sustainability of freight transport within the supply chain. The British rail network has seen considerable growth of both freight and passenger activity in the last 20 years, leading to concerns about its capacity to absorb continued growth. A number of infrastructure initiatives focused on increasing capacity and reducing conflicts have been implemented. This includes the North Doncaster Chord, opened in June 2014 primarily to provide a more direct route from the port of Immingham to the major Aire Valley power stations (i.e. Drax, Eggborough and Ferrybridge). The paper analyses the freight impacts of the new chord, focusing on three key operational measures (i.e. train routing, scheduled journey times and train punctuality) during 10-week survey periods before and after the opening of the chord. The analysis is based on real-time data relating to coal and biomass trains operating between Immingham and the three power stations. This is a novel approach as the data have been made publicly available only recently, allowing a detailed investigation of the flows on this corridor at a highly disaggregated level. The use of this empirical method to assess the detailed rail freight operational impacts is an important element in the process of evaluating the effects of network enhancement. The results demonstrate improvements in each of the three operational measures, but also reveal a situation considerably more complex than that suggested by the published material relating to the justification for this new infrastructure. Highlights: Network enhancements an important element in improving rail freight performance Detailed investigation of new infrastructure initiative in the United Kingdom Innovative, replicable methodology using real-time train running data Observed improvements in train routing, scheduled journey times and train punctuality